Malaria Prevention Strategies in Kalimantan, Indonesia: A Secondary Analysis of 2018 Basic Health Research Data - Ridha, Muhammad Rasyid; Andiarsa, Dicky; Noor, Ihya Hazairin; Wiliyani, Erni; Ramadhani, Tri; Yudhastuti, Ririh (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2024)
Background: Kalimantan remains malaria-endemic, particularly in rural areas, where prevention efforts face challenges such as insecticide resistance and limited healthcare access. Despite available measures like insecticide-treated nets, gaps in understanding individual and household prevention practices persist, especially in relation to demographics and effectiveness in reducing malaria transmission.Purpose: This study aimed to examine the individual and household-level malaria prevention strategies utilized in rural Kalimantan and evaluate their effectiveness in reducing malaria incidence.Methods: The study was a secondary analysis of the 2018 Indonesian basic health research (Riskesdas). A total of 67,155 respondents in Kalimantan were analyzed including respondent characteristics, memories of malaria infection, and individual and household malaria prevention efforts. The data were collected through the result of the 2018 Riskesdas survey. Bivariate regression and multivariable logistic regression were used in data analysis.Results: Self-reported malaria rates were higher among older respondents compared to younger ones. Women reported lower malaria rates than men, especially in South Kalimantan. In West Kalimantan, the use of bed nets was associated with higher self-reported malaria rates (OR=1.838, 95%CI 1.147–2.943). Short-term use of insecticide-treated nets (ITNs) showed varying odds across provinces: Central Kalimantan (OR=3.659, 95%CI 1.378–9.717), South Kalimantan (OR=10.811, 95%CI 3.649–32.030), East Kalimantan (OR=2.615, 95%CI 1.041–6.567), and West Kalimantan (OR=2.428, 95%CI 1.446–4.078). In all provinces, preventive measures such as coils or electric mats reduced self-reported malaria cases. The use of mosquito screens was effective in South Kalimantan (OR=0.208, 95%CI 0.027–1.598), Central Kalimantan (OR=0.365, 95%CI 0.120–2.181), and North Kalimantan (OR=0.000, 95%CI 0.000–0.000). The multivariate model highlighted mosquito nets as the most effective household-scale prevention in nearly all Kalimantan provinces except North Kalimantan.Conclusion: This study showed that individuals aged 25 and over, women, non-farmers, and those using ITNs and other preventive measures, especially in rural areas, were less likely to report malaria, emphasizing the need for targeted interventions from local health authorities.